Catalytic Production of Glucose–Galactose Syrup from Greek Yogurt Acid Whey in a Continuous‐Flow Reactor. Issue 4 (21st January 2020) - Lindsay, Mark J.; Huang, Kefeng; Buchinger, Brent A.; Maravelias, Cristos T.; Dumesic, James A.; Rankin, Scott A.; Huber, George W.
Abstract: The hydrolysis of lactose in aqueous solutions and dairy waste streams was studied using Amberlyst 70 as a heterogeneous acid catalyst in a continuous‐flow packed‐bed reactor. The catalyst was stable during hydrolysis of an aqueous lactose feed but deactivated owing to mineral poisoning when the dairy waste Greek yogurt acid whey (GAW) was used as the feedstock. A catalyst deactivation model was developed and showed that the deactivation of the Amberlyst 70 catalyst was proportional to the amounts of cations, urea and amino acids flowing through the catalyst bed. The Amberlyst 70 catalyst was regenerable with an aqueous acid regeneration treatment. Based on the experimental data, a rigorous technoeconomic analysis was performed for the production of glucose–galactose syrup (GGS) via lactose hydrolysis of GAW using three different catalysts. This approach shows that the GGS produced from GAW could become a valuable revenue stream for Greek yogurt manufacturers. Abstract : A better whey : The hydrolysis of lactose in dairy waste streams, catalyzed by the solid acid catalyst Amberlyst 70, can produce a sweetener syrup for use by food and biotech industries. Amberlyst 70 achieves 99 % selectivity to monosaccharides even at >90 % conversion. A technoeconomic analysis shows that this syrup can be economically viable.